Health Care Insurance and Moral Hazard - Hong Mao; Jin Wang (Randwick International of Social Science Journal, 2021)
In this article, we discuss how moral hazard affects health care insurance, the social benefit and the harmfulness of moral hazard in health care insurance. We also discuss the relationship between copayment rate and decease risks and indicate that it is necessary to reduce copayment ratio for serious decease in social health care insurance in order to generate social gain. Finally, we carry out sensitivity analysis to illustrate the effect of the change of important parameters on optimal copayment rate.